Analisis kesesuaian dan daya dukung ekowisata bahari Pulau Sebesi, Provinsi Lampung - Yar Johan (Depik Jurnal, 2015)
Abstract. The Sebesi Island has coral reefs, mangrove and seagrass ecosystems, and therefore this island has the potenticy to be developed as a tourism destination object. The objectives of the present study were to analysis the suitability and carrying of Sebesi Island for for marine ecotourism activities of diving and snorkeling. The primary data were collected through field sampling, direct observation of field conditions, questionnaires and interviews. The secondary data were collected from previous studies, journals, technical reports and related agencies. The results showed that the Sebesi Island was suitable for diving and snorkeling activities  (S2 category) with the carrying capacity for diving and snorkeling activities were 2,394 person/day and 2,489 person/day, respectively.